AB0860 Prevalence of Risk Factors for Gastrointestinakl Side Effects Of Drugs for the Treatment of Pain in Rheumatic Diseases and the Provisions of Gastroprotective Treatment – Results of a Large Non Intervention Study. (9th June 2015) - Robles, M.; Citera, G.; Rillo, O.; Smecuol, E.; Millán, A.; Mantilla, R.
Abstract : Methods: The RATIONAL study had an observational, multicenter, multinational, cross-sectional design to evaluate the prevalence of GI risk factors in patients with osteoarthritis (OA), rheumatoid arthritis (RA) and ankylosing spondylitis (AS). The single study visit was part of standard practice. Patients were aged >21 years with a documented diagnosis of RA (ACR 1987 or ACR/EULAR 2010 criteria), OA (ACR 1986, 1990 and 1991 criteria) or AS (New York 1984 criteria or ESSG 2002 criteria) and had taken at least one dose of NSAIDs in the 15 days before enrolment. Information collected included NSAID treatment over the year preceding the study visit, GPA use, and occurrence of any of a defined range of GI events. Results: The distribution of rheumatic disorders in the 5373 patients was OA 2996 (55.8%), RA 1882 (35.0%), AS 283 (5.3%), and a combination of these 212 (3.9%). Most patients had one (34.2%) or two (32.0%) defined GI risk factors. The prevalence of individual risk factors and treatment with GPAs is shown in the Table. GPA use in patients aged ≥60 years or concomitantly using anticoagulants was close to the study average (57.9%). A modest numerical increase from this mean value was observed in patients taking concomitant ASA (63.8%) or high doses of an NSAID (64.1%). A greater numerical increase in this percentage was seen for all of the other risk factors with values of 96.6% and 93.3% for those with histories of GI complications and GI ulcer, respectively. There was a strong preference for using proton pump inhibitors (PPIs) as the class of GPA and the most commonly used individual treatment was omeprazole (36.4% of total patients). Conclusions: The association of NSAID with BIP protects the gastric damage. Disclosure of Interest: None declared